If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -6 = -5 Reorder the terms: -6 + 15y = -5 Solving -6 + 15y = -5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 15y = -5 + 6 Combine like terms: -6 + 6 = 0 0 + 15y = -5 + 6 15y = -5 + 6 Combine like terms: -5 + 6 = 1 15y = 1 Divide each side by '15'. y = 0.06666666667 Simplifying y = 0.06666666667
| 9(t-3)+3t=4(3t+4)-12 | | 6.99+.55c=11.94 | | 3t-6t=27 | | -4(-5-8n)+5n= | | x=(20-y)-(20-z) | | x+4.2=27.8 | | 79+9x+6x-4=180 | | 6.99+.55=11.94 | | 12x+4+11x+12=90 | | -2x+0=-2x | | c+(-3)=100 | | x+27.3=14.2 | | 3+4+2x-1=18 | | 3+6(8x+3)= | | f(x)=0.08x^3+x^2+x+0.26 | | 2(x-5)-4x=-7 | | 4x-107-12x=125 | | -x-4y=-20 | | 7r^2+2r-5=0 | | 1x+11+8x=20 | | f(m)=m+4 | | -37+x=123 | | 2x+12=-7x-19 | | 3(4+w)=3(w+4) | | f(10)=0.08x^3+x^2+x+0.26 | | 9x-3+5x+8=15x | | -2(1+6x)-3= | | 3x+12=69 | | 11=2(w-2)+2w | | 10b-10=9b | | -5(9p-4)= | | 48n^2-6=-42n |